The Concept of Emergency in Finnish Emergency Legislation : An Analysis of Amendments to the Emergency Powers Act - Brunila, Tuukka (Faculty of law Lund University, 2026)
In this article, I analyse the expansion of concept of emergency in the Finnish legal system by means of amending the Emergency Powers Act (1552/2011). The Act is the one of the main vehicles for regulating the use of emergency powers. The Act lists six distinct exceptional circumstances that authorise a state of emergency. Amendments to the Act have served to expand the definition of emergencies in the Constitution (Section 23) and the concept of emergency in general. By analysing the travaux préparatoires of relevant amendments, the focus is on the principles in expanding the concept. I argue that one of the main principles in developing the concept through legislation is preciseness. Emergencies should have to be defined by means of legislation as precisely as possible. In analysing the main principles in expanding the concept of emergency, this article seeks to also emphasise the tensions between these principles. As I will point out, sometimes preciseness is outweighed by the need to ensure that the Act accommodates all emergencies exhaustively.